(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This work is devoted to the study of euphemism in the language of modern British, American and Russian press. Euphemia is closely related to the media. Thanks to this, euphemisms become extremely widespread in socially significant areas of speech activity